Mechatronic device of AI systems - A. Y. Kulsha; M. A. Klimovich; M. V. Sterjanov; V. N. Tesluk; N. G. Egorova (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The purpose of this work is to demonstrate the phased development of a mechatronic device, to describe the development process of the device design and software, to demonstrate the application of the theory of selected sections of mathematics and physics in robotics, and, in particular, linear algebra, geometry, computational mathematics, discrete mathematics and mechanics. The study was based on the mechatronic device, which had been designed by the youth team of the Republic of Belarus in preparation for the international robotics competition “First Global Challenge 2019”, which became the winner of this event. The article describes in detail the statement of the problem at this competition, identifies the basic requirements for the robot being built, provides a general description of the stages of building the device both during the design process and during the immediate implementation of the project, as well as substantiates the engineering decisions that were made during the design process. The stages that are of the greatest interest in terms of applying the theory of applied physics and mathematics are described in more detail. Particular attention is paid to the design and development of structural modules, as well as to the development of software for controlling the device. The robot is an experimental model that can be used in further research in the field of artificial intelligence, machine learning, automation systems, and is also a potential platform for teaching robotics at the level of specialized secondary and higher education.